Nové moznosti ockování proti chripce - Chlíbek, R (Casopis lekaru ceskych, 2010)
One of the ways to increase a low rate of vaccination against the flu in the Czech population is using new vaccination methods, e.g. the intradermal flu vaccine application method. This method uses a high skin immune potential, where a great amount of dendritic cells, macrophages, lymphocytes as well as abundant capillary and lymphatic supply can be found. A progressive microneedle application system allows the accurate application right into the dermis and a dosage consistency without any necessity of much experience and training in intradermal administration. Comparable results of immunogenity with lower antigen content and less vaccine amount are reached with intramuscular application in adults up to 59. Using the same antigen amount as in intramuscular application in people older than 60, significantly better results are reached. A new intradermal vaccine IDflu is registered in Europe for people from the age of 18 and it is considered to be a new alternative way to raise popularity of flu vaccination in lay and professional public. The microneedle intradermal application system brings an easier way of vaccination for doctors with application of less amount of vaccine and there is no need to remove air from the syringe and no need of aspiration. The vaccine will be introduced in the Czech market before the flu season 2010/2011.
Keywords: vakcíny proti chřipce; injekce intradermální; lidé; Humans; Influenza Vaccines; Injections, Intradermal